Analisis Keterlaksanaan Penilaian Keterampilan Kurikulum 2013 Pada Guru SD Se-Kecamatan Batang - Rochamin; Rasiman; Ida Dwijayanti (JANACITTA, 2023)
The purpose of this research is; to describe and obtain information, how is the implementation of skills assessment in the 2013 curriculum; to describe and obtain information, what factors influence the implementation of skills assessment in the 2013 curriculum; to describe and obtain information, what obstacles exist in the implementation of skills assessment in the 2013 curriculum.In this study, the researcher acted as a key instrument as well as a data collector. The instruments used are interviews, observations, and documents. The presence of researchers in this study was as participant observers and their status as informants. In this study, the main data collection techniques were semi-structured interviews, frank and vague observation, and document study. For semi-structured interviews, the researcher interviewed teachers in the dabin, as well as document studies.Professional teachers are required not only to have teaching skills as required in the pedagogic competency standard, but teachers must also be able to develop professionalism continuously as stated in professional competence. From the results of the implementation research, the skills assessment was less than optimal. This can be seen through observations and interviews that the researchers conducted with the informants. Factors for the implementation of skills assessment in the 2013 curriculum include teacher creativity, teacher preparation, student preparation, student enthusiasm for learning, facilities and infrastructure. while the obstacles to the implementation of the skills assessment in the 2013 curriculum included the teacher's lack of understanding of the material, the material being taught a lot, students' abilities varied, and pursuing material so that it was finished.   Tujuan penelitian ini adalah; untuk mendeskripsikan dan memperoleh informasi, bagaimanakah keterlaksanaan penilaian ketrampilan pada kurikulum 2013: untuk mendeskripsikan dan memperoleh informasi, faktor – faktor apa sajakah yang mempengaruhi pelaksanaan penilaian ketrampilan pada kurikulum 2013; untuk mendeskripsikan dan memperoleh informasi, hambatan apakah yang ada dalam pelaksanaan penilaian ketrampilan pada kurikulum 2013. Pada penelitian ini, peneliti bertindak sebagai intrumen kunci (key Instrument) sekaligus sebagai pengumpul data. Instrumen yang digunakan adalah Wawancara, observasi, dan dokumen. Kehadiran peneliti dalam penelitian ini adalah sebagai pengamat partisipan dan statusnya sebagai informan.  Pada penelitian ini teknik pengumpulan data yang utama dengan cara wawancara semitersetruktur, observasi terus terang dan samar, serta study document. Untuk wawancara semiterstruktur peneliti mewawancarai  guru yang ada pada dabin tersebut, serta study document. Dari hasil penelitian ini yakni keterlaksanaan penilaian keterampilan kurang maksimal, hal tersebut dapat diketahui melalui observasi dan wawancara yang peneliti lakukan terhadap narasumber. Faktor – faktor keterlaksanakan penilaian keterampilan pada kurikulum 2013 antara lain, kreatifitas guru, persiapan dari guru, persiapan dari siswa, semangat belajar siswa, sarana dan prasarana. sedangkan hambatan – hambatan keterlaksanaan penilaian keterampilan pada kurikulum 2013 antara lain kurang pahamnya guru terhadap materi, materi yang diajarkan banyak, kemampuan siswa berbeda – beda, dan mengejar materi supaya habis.